The Herbivorous Butcher cookbook : 75+ recipes for plant-based meats and all the dishes you can make with them - Walch, Aubry; Walch, Kale; Seo, Danny; Soria, Sandra S. (Chronicle Books, 2022)
"75 innovative recipes for plant-based meats and standout vegan dishes from The Herbivorous Butcher Shop"--